Automatic Book Rack System with Expandable Clasp Holder: A Short Review - Pathak, Aniket; Fernandez, Wilfred; Mistry, Hit; Oommen, Nithin; Dabla, Ravi (Advanced Aspects of Engineering Research Vol. 4, 2021)
In the light of number of universities and libraries consistently increasing and book storage/ maintenance becoming a difficult task, there is a need to design a system which will reduce manual work as well as minimise the problem of using the book racks. The review is done to identify the various shortcomings of the present system and overcome the flaws faced such as accessing books at height, cleaning the shelves at the topmost compartment and holding the books upright in proper position. The automatic book rack system includes shelf, expandable clasp housing that is movable and connected to the shelf. The housing includes a noiseless electric motor and a pair of chain and sprockets. The electric motor, chain sprockets work in conjunction to achieve linear motion of the housing along the shelf. The expandable clasp can support the books in an upright, side by side arrangement on the shelf. Once a book is removed from the shelf the clasp housing is automatically repositioned to push the remaining books together and close any resulting gaps between the remaining books keeping them upright. Exemplary systems according to present disclosure include the mechanism that permit reliable and efficient repositioning of one or more shelves, thereby enhancing utilization and efficiencies associated therewith. For completion of this task we have successfully designed the automatic book rack and with suitable material selection the ABR system has been fabricated.